Proteotranscriptomic Profiling of the Toxic Mucus of Kulikovia alborostrata (Pilidiophora, Nemertea) - Vasiliy G. Kuznetsov; Daria I. Melnikova; Sergey V. Shabelnikov; Timur Yu. Magarlamov (Toxins)
Nemertea is a phylum of bilaterally symmetrical, coelomate, unsegmented worms, also known as ribbon worms. Most species of the phylum Nemertea are marine predators that contain toxins in the single-celled glands of the proboscis and/or integument. Recent transcriptomic studies have shown that nemerteans from all taxonomic groups possess a wide range of putative protein and peptide toxins, while the proteomic data for these animals are highly limited. In this study, proteotranscriptomic analysis was used to investigate the major protein components of the poison of the nemertean Kulikovia alborostrata. We identified 146 transcripts of putative toxins in the transcriptome of K. alborostrata and five putative toxins among the secreted proteins and peptides of the mucus of the animal. The expression levels of cysteine-rich peptides found in the mucus with similarity to known toxins were evaluated in different parts of the body of the worm by quantitative real-time PCR. The high level of expression of investigated peptides in the integument indicate the protective function of these toxins. Overall, this supports the idea that the mucus of nemerteans is a valuable source of peptide and protein toxins.